Comparative analysis of exercise equipment jerk in weightlifting and weight sport - V.Y. Djim (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The approaches to the analysis of exercise equipment in weightlifting and weight sport. The method of photographic images and analysis videogram movement. Exercise performed once with the weights of 50, 65 and 75% of the maximum limit. Kettlebell snatch carried out using two dumbbells weighing 32 kg each. An improved technique spurt in which efficiency is the greatest. It is noted that under the dash with undergrowth performed the lead from the platform heels. This technique does not allow the movement of the full potential of the athlete. 'Technique of the jerk with full support legs for the entire period lifting a barbell. Found that it reduces the lift rod and provides the trajectory of the rod with the continuous growth to its final value.